Participatory Forest Management to meet Basic Needs of Forest Dependent Communities - , Pratima; Jattan, S. S. (Indian Forester, 1999)
In pursuance of the National Forest Policy, 1988 provision to create a massive people’s movement for the conservation of forest resources, Joint Forest Management (JFM) approach has been adopted in the country to protect and rehabilitate the degraded forests. The paper analyses the working of JFM and summarises the experience gained. Based on the past experience, suggestions are made to improve the implementation of JFM.